Investigation of Effects of Mig Welding on Corrosion Behaviour of AISI 1010 Carbon Steel - Nur Azhani, Abd Razak; Shing Shian, Ng (Faculty Mechanical Engineering, UMP, 2014)
This paper presents the corrosion behaviour of welded low carbon steel at different welding voltages and filler materials. The welding process was conducted on butt joint specimens using the metal inert gas (MIG) technique at a welding voltage range of 19 to 21 V with 1 V interval, and the filler materials used were ER 308L and ER 70S-6 with 1.2 mm diameter. Heat treatment through full annealing was done to the welded low carbon steel, and the corrosion behaviour was tested using a synthetic seawater environment with 3.5 wt% NaCl. Microstructure changes were observed using a scanning electron microscope (SEM). The results showed that the corrosion rate decreased when the welding voltage increased, as it directly affected the welding heat input. The welding heat input was found to have a significant effect on the corrosion rate as it changed the ferrite content in the microstructure of the specimens. Decrease in the corrosion rate was also found when the full annealing process was done to the specimens and ER 308L filler material was used. From a metallographic study, iron oxides and pitting were found on the surface of the exposed area after the corrosion test. It is apparent that the combination of higher welding voltage, heat treatment and the use of ER 308L filler material can reduce the corrosion rate of AISI 1010 carbon steel.